Формування російської програми врегулювання Східного питання (березень-квітень 1876 р.): на основі документів Архіву зовнішньої політики Російської імперії - Гончаренко, А.В. (Сумський історико-архівний журнал, 2010)
After analyzing the documentary sources the author makes an attempt of tracing the process of forming the streams of Russian diplomacy concerning settling “The Eastern question” in the spring of 1876.